(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Sweet potato is a source of protein and energy in the human diet. To increase its industrial application, sweet potato flour (SPF) has been produced for use in bakery products. The effect of inclusion of SPF in bread making at different wheat-potato blend ratios was studied. SPF was produced by washing, peeling, blanching, cutting, drying and milling (in that order) of the freshly harvested potato roots. Bread samples were produced from the blend of SPF and wheat flour at the following ratios: 5:95, 10:90, 15:85 and 20:80 respectively with bread from 100% wheat serving as control. Proximate analysis, anti-nutrient analysis and sensory evaluation were carried out on the bread samples while the wet gluten content and water absorption capacity was carried out on the flour sample. The result of the proximate composition showed that, as SPF percentage increased, moisture, protein, fat and fibre of bread increased while ash and carbohydrate decreased. Wet gluten decreased and water absorption capacity increased as the SPF increased with values ranging from 20.11 - 10.00g/100g and 50.65 - 80.65ml/100g respectively. The phytate, tannins and phenolic content were at the range of 0.10 - 0.27mg/g, 0.09 - 0.28mg/g, and 0.27 - 0.31mg/100g respectively. For sensory evaluation, though the control sample was the most preferred, no panellist showed a dislike for any attribute evaluated in the substituted samples. Hence, SPF could be used to substitute up to 20% of wheat flour in bread making without adversely affecting the quality or acceptance of the bread.